The manifestations of autoimmune processes in the ovaries in women with pelvic inflammatory diseases - M. L. Dmitriyeva; O. A. Tikhonovskaya; S. A. Nevostruyev; S. V. Logvinov; T. V. Tupitsyna (Бюллетень сибирской медицины)
A retrospective analysis of clinical and laboratory data of women with inflammatory diseases of the pelvic organs was performed. It was shown that the inflammatory changes of genital tract and pelvic adhesions lead to the development of autoimmune ovarian lesions.